The Existence of Islamic Law in The Legal System And Constitution in Indonesia: Reflection of Islamic Legal Thought and Positive Law - Mustafa; Soge, Albertus D; Edy, Slamet Sarwo (Jurnal Hukum Caraka Justitia, 2025)
The legal position of Islam in the Republic of Indonesia cannot be separated from the influence of the entry of Islam throughout the archipelago around 16-17 Hijri, where at that time the spreaders of Islam throughout the archipelago came from various Middle Eastern countries, such as India, Pakistan, Arabia, Egypt, Jordan, and others, they traded to the archipelago while spreading Islam, and on average they brought the Shafi'i school of thought. The historical journey of the transformation of Islamic Law with various dimensions, namely; historical, philosophical, political, sociological, and legal. The presence of Islamic Law in Indonesia can be seen from two sides, namely: Islamic law applies legally formally or codified in the National legal structure, so the current compilation of Islamic Law was born which recorded the regulations of Islamic Law that have been enforced so far. And Islamic Law applies normatively, namely; having sanctions or legal equivalents for the Muslim community. The 1945 Constitution, Indonesia's constitution, also expresses the character and spirit of Islam, a constitution that is neither theocratic nor secular.